2018
DOI: 10.1093/conphys/coy010
|View full text |Cite
|
Sign up to set email alerts
|

Elevated temperatures are associated with stress in rooftop-nesting Common Nighthawk (Chordeiles minor) chicks

Abstract: Common Nighthawk (Chordeiles minor) nesting habitat is limited to urban rooftops in southeastern South Dakota. Regional climate has changed from 1948 to 2016, with increases in humidity and solar radiation. Chicks exposed to high temperatures showed high baseline plasma corticosterone and low stress responses, suggesting that current climate influences stress response capacity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 57 publications
0
9
0
Order By: Relevance
“…89 Study site and system 90 Fieldwork was conducted at the Kuruman River Reserve (33 km 2 , KRR; 26°58'S, 91 21°49'E) in the southern Kalahari. Mean summer daily maximum temperatures at the study site, 92 from 1995-2015, averaged 34.7 ± 9.7°C and mean annual precipitation averaged 186.2 ± 93 87.5mm [49].…”
Section: Methodsmentioning
confidence: 99%
“…89 Study site and system 90 Fieldwork was conducted at the Kuruman River Reserve (33 km 2 , KRR; 26°58'S, 91 21°49'E) in the southern Kalahari. Mean summer daily maximum temperatures at the study site, 92 from 1995-2015, averaged 34.7 ± 9.7°C and mean annual precipitation averaged 186.2 ± 93 87.5mm [49].…”
Section: Methodsmentioning
confidence: 99%
“…At high temperatures over prolonged periods, incubating birds may not be able to sustain nest attendance to regulate egg temperature [81], leaving eggs vulnerable to overheating and becoming unviable [15,76]. Likewise, several studies have reported that high temperatures constrain nestling growth [24,77,82], result in smaller nestlings overall [25,83,84], alter corticosterone levels [85,86] and reduce nestling survival probabilities [87,88]. Rainfall was the strongest predictor of survival probability during the dependent fledgling stage.…”
Section: (A) Impacts Of High Temperatures During Early Developmentmentioning
confidence: 99%
“…Adverse weather conditions impair nestling development Imlay et al 2018) by causing a trade-off between devoting energy to thermoregulation or to growth (Dawson et al 2005). High temperatures constrain nestling growth (Cunningham et al 2013;Andreasson et al 2018), result in smaller nestlings overall (Salaberria et al 2014;Wada et al 2015;Rodriguez and Barba 2016), alter corticosterone levels (Newberry and Swanson 2018;Crino et al 2020) and reduce survival probabilities (Greño et al 2008;Zuckerberg et al 2018;Bourne, Cunningham, et al 2020a). Higher rainfall often has a positive effect on nestling development (Wiley and Ridley 2016) and survival (Skagen and Yackel Adams 2012;Mares et al 2017), at least in arid and semi-arid ecosystems (Cumming and Bernard 1997;Hidalgo Aranzamendi et al 2019), although see Morganti et al (2017) and Cox et al (2019) for effects of rainy weather in temperate environments.…”
Section: Introductionmentioning
confidence: 99%